2016
DOI: 10.1038/nn.4297
|View full text |Cite
|
Sign up to set email alerts
|

Sequential regulatory loops as key gatekeepers for neuronal reprogramming in human cells

Abstract: Direct conversion of somatic cells into neurons holds great promise for regenerative medicine. However, as neuronal conversion is relatively inefficient on human cells compared to mouse cells, it has been unclear what might be key barriers to reprogramming in human cells. We recently elucidated an RNA program mediated by the polypyrimidine tract binding protein PTB to convert mouse embryonic fibroblasts (MEFs) into functional neurons. On human adult fibroblasts (HAFs), however, we unexpectedly find that invoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
104
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 54 publications
8
104
2
Order By: Relevance
“…Follow-up studies showed that while miR-9 is not necessary for the early neural induction phase, it is required to obtain fully mature iNs from human fibroblasts 70,71 . The function of miR-9 during iN maturation was linked to a repression of the mRNA splicing regulator PTBP2 by miR-9 71 . However, considering the broad target repertoire of miR-9, which includes several key neuronal fate regulators, it is conceivable that other target genes contribute to the consolidation of neuronal differentiation in this conversion paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up studies showed that while miR-9 is not necessary for the early neural induction phase, it is required to obtain fully mature iNs from human fibroblasts 70,71 . The function of miR-9 during iN maturation was linked to a repression of the mRNA splicing regulator PTBP2 by miR-9 71 . However, considering the broad target repertoire of miR-9, which includes several key neuronal fate regulators, it is conceivable that other target genes contribute to the consolidation of neuronal differentiation in this conversion paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…The forced expression of miR124 and another neuron-specific microRNA, miR9/9*, is sufficient for the cells converted from adult fibroblasts to adopt neuronal features [14]. In line with this, it was shown that the combination of miR9/9* and miR124 can accelerate neuronal conversion [23,24]. The effect of short hairpin-mediated knockdown of REST (RESTi) on neuronal conversion efficiency is mediated at least in part via the upregulation of miR9 and miR124 as an effect of RESTi, but it is becoming clear that RESTi also acts via microRNA-independent pathways [22].…”
mentioning
confidence: 69%
“…The effect of short hairpin-mediated knockdown of REST (RESTi) on neuronal conversion efficiency is mediated at least in part via the upregulation of miR9 and miR124 as an effect of RESTi, but it is becoming clear that RESTi also acts via microRNA-independent pathways [22]. In line with this, it was shown that the combination of miR9/9* and miR124 can accelerate neuronal conversion [23,24]. However, the interplay between RESTi and neuronspecific miR9 and miR124 in morphological and functional maturation of iNs has yet to be fully understood.…”
mentioning
confidence: 98%
“…The PTB-REST-miR-9/9*-124 ensemble is so powerful that mere interference with it, through shRNA-mediated knockdown of PTBs or components of the REST complex or through overexpression of miR-9/9*-124, can replace pioneer transcription factors (Fig. 1A) [38,[42][43][44][45]. Similar to Ascl1 alone, also shRNA-only and miRNA-only iN protocols are quite inefficient and rely on several 'helper' factors ( Fig.…”
Section: Enabling In Conversionmentioning
confidence: 99%